2015
DOI: 10.1021/acs.molpharmaceut.5b00043
|View full text |Cite
|
Sign up to set email alerts
|

Zeolitic Imidazole Framework (ZIF) Nanospheres for Easy Encapsulation and Controlled Release of an Anticancer Drug Doxorubicin under Different External Stimuli: A Way toward Smart Drug Delivery System

Abstract: The conventional drug delivery systems made from organic- or inorganic-based materials suffer from some problems associated with uncontrolled drug release, biocompatibility, cytotoxicity, and so forth. To overcome these problems, zeolitic imidazole framework (ZIF) hybrid materials can be one of the solutions. Here, we report a very easy and successful encapsulation of an anticancer drug doxorubicin inside two ZIFs, namely, ZIF-7 and ZIF-8, which are little explored as drug delivery systems, and we studied the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(95 citation statements)
references
References 50 publications
2
92
0
1
Order By: Relevance
“…Similarly, these authors have also described two DOX-loaded ZIFs (ZIF-7 and ZIF-8) for the liposome-responsive release of DOX. [83] The loading capacity of DOX into ZIF-7 and ZIF-8 was approximately 40% and 52%, respectively, the difference being due to ZIF-7 having a bigger cavity size than ZIF-8. This study showed that both ZIFs were excellent for DOX release when in contact with liposomes.…”
Section: Liposome-responsive Mofsmentioning
confidence: 95%
“…Similarly, these authors have also described two DOX-loaded ZIFs (ZIF-7 and ZIF-8) for the liposome-responsive release of DOX. [83] The loading capacity of DOX into ZIF-7 and ZIF-8 was approximately 40% and 52%, respectively, the difference being due to ZIF-7 having a bigger cavity size than ZIF-8. This study showed that both ZIFs were excellent for DOX release when in contact with liposomes.…”
Section: Liposome-responsive Mofsmentioning
confidence: 95%
“…[27] However, it is not stable in acidic environments because of the loss of the coordination between the zinc ions and imidazolate at pH 5.0–6.0. [28] Therefore, as long as ZIF-8 protected surfaces are stored in dry or nonacidic conditions, the ZIF-8 shell should be stable. For the same reason, water at pH 6 was employed to completely remove the ZIF-8 protective layer and restore the biofunctionality of antibodies conjugated to nanotransducers.…”
mentioning
confidence: 99%
“…Comparison to a mere physical mixture of the two components i. e., ZnO@ZIF‐8 and antibiotic, the present approach has integrated some key advantages. For instance, the crystalline nature of the ZIF‐8 shell will allow the controlled release of the antibiotic molecules . Additionally, the structural susceptibility of ZIF‐8 shell towards the acidic environment will ensure a pH‐responsive release mechanism of antibiotics which becomes particularly relevant for wound healing applications where the pH of the environment has a direct implication in the healing process .…”
Section: Resultsmentioning
confidence: 99%